Joko Widodo Dalam Bingkai Harian Umum Republika - Suharyo Suharyo (Nusa: Jurnal Ilmu Bahasa dan Sastra, 2017)
This study aims to describe how the daily Republika frames President Joko Widodo. To disclose, simak method followed by noting technique – as described by Sudarjanto (1993) – will be used, while the framing model by Pan Kossicki will be used for the analysis. As a result, President Joko Widodo is positively framed through (a) a syntactic structure that includes the title diction he chooses, leads, backgrounds, source uses, and positive news cover; (B) structure of the script making full use of the 5W 1H element, (3) the thematic structure seen through President Joko Widodo's message which is packed with a polite diction, such as "the student should focus more on the more productive use of energy, such as"; And (4) rhetorical structure seen through the photo placement of Joko Widodo increasingly clarify the message that wants to be delivered by Jokowi